2022
DOI: 10.1371/journal.pgph.0001342
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of blood pressure and blood glucose control in patients with co-morbid hypertension and type 2 diabetes mellitus in Ghana: A hospital-based cross-sectional study

Abstract: Hypertension and diabetes are major risk factors for cardiovascular diseases and optimal control of blood pressure (BP) and blood glucose are associated with reduced cardiovascular disease events. This study, therefore, sought to estimate the prevalence and associated factors of controlled BP and blood glucose levels among patients diagnosed with both hypertension and Type 2- diabetes mellitus (T2DM). A quantitative cross-sectional study was conducted in a primary health setting in Ghana among patients 18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…However, it is also well-known that the factors for reducing blood sugar are complex and can be caused by other factors, including demographic characteristics and lifestyle (Alhassan et al, 2022). In this current study which involved prediabetic patients, the majority of subjects were adults aged 16-45 years and 75% were women.…”
Section: Resultsmentioning
confidence: 78%
“…However, it is also well-known that the factors for reducing blood sugar are complex and can be caused by other factors, including demographic characteristics and lifestyle (Alhassan et al, 2022). In this current study which involved prediabetic patients, the majority of subjects were adults aged 16-45 years and 75% were women.…”
Section: Resultsmentioning
confidence: 78%
“…Co-morbid hypertension and diabetes patients often require more prescribed medications, leading to increased medication-related burden. 16 , 20 , 52 , 53 To address this, it is crucial to streamline treatment regimens, use combination medicines when suitable, and ensure patients receive sufficient knowledge about their condition and medication. 50 , 54 Effective medication management requires a collaborative approach involving patients and healthcare practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure and glucose levels that are well-managed contribute to reduced symptoms, enhanced energy, and improved mental health. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…While the role of diet, physical activity, medication, and regular screenings is acknowledged, social, cultural, and economic factors, as well as awareness of one's diabetic status, significantly influence health behaviours (19). Previous studies conducted in Ghana have identified barriers to diabetes prevention and management, including perceptions of risk, resistance to behaviour change, social stigma, psychosocial burden, economic constraints, medication non-adherence and limited access to healthcare facilities and nutritious foods (20)(21)(22). Addressing these challenges necessitates the development of cost-effective diabetes prevention programs tailored to the Ghanaian population.…”
Section: Introductionmentioning
confidence: 99%